Schenkungen und Erbschaften im Lebenslauf: vergleichende Längsschnittanalysen zu intergenerationalen Transfers - Thomas Leopold; Thorsten Schneider (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
– The research on private financial transfers between generations lacks a longitudinal perspective. Gifts as intergenerational transfers inter vivos allow us to study the importance of life course events for the chances of receiving transfers. In Germany, gifts are highly private and leave more scope for decision-making than the regulated bequests. Thus, gifts are better suited to test theories on family solidarity and transfer behavior. Our analysis focuses on larger transmissions, which parents and grandparents give to their descendents. Bequests provide a comparative reference to highlight similarities and differences between transfers inter vivos and mortis causa. In our account, gift-giving is purposive action driven primarily by economic needs of the receivers, but also by non-material aspects of family ties. Bequeathing is characterized as behavior which is not necessarily purposive and highly restricted by normative and legal obligations. Hypotheses for both types of transfers are tested with retrospective data from the German Socio-Economic Panel (SOEP). We use event history models to study the effects of changes in the life course on the chances of receiving transfers. Increased chances to receive a large gift occur in the first years after marriage and also immediately after divorce. Women are clearly disadvantaged as their chances to receive a gift and the transfer amounts are considerably lower. In low status families, large transfers inter vivos are a rare event. If they occur, these gifts often replace bequests. In high status families, gifts are transferred more frequently, and often as a complement to subsequent bequests.
Keywords: D10; J10; C41; 330; Bequests; gifts; transfers; intergenerational solidarity; duration analysis